2021
DOI: 10.17503/agrivita.v43i1.2796
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Foliar Application Chitosan and Salicylic Acid on Physiological Characteristics and Yield under Deficit Irrigation Condition

Abstract: Moreover, drought stress increases the amount of abscisic acid in the plant, which reduces the growth rate (Siebeneichler et al., 2020).Research has shown that chitosan consumption is common in living organisms, including plants (Ngo et al., 2015). Chitosan boosts plants' defenses and can even increase resistance to plant pathogens (Sharma et al., 2019). Chitosan is derived from chitin, which is an antitoxic substance. Especially in low doses, chitosan can improve a plant's resistance to pathogens by strengthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Salicylic acid and its derivatives sprayed on the leaves increased drought tolerance in Basella experiencing dry stress. Research shows that the application of salicylic acid (Morovvat et al 2021) reported treatment of potatoes showed a significant effect on the water supply status of the plants; the effect of salicylic acid on irrigation treatment 60 and 80% showed an increase in potato yields under severe drought stress conditions. The best yield treatment was salicylic acid treatment with 100% irrigation.…”
Section: Interaction Effect Between Ds and Sa On Growth And Photosynt...mentioning
confidence: 99%
“…Salicylic acid and its derivatives sprayed on the leaves increased drought tolerance in Basella experiencing dry stress. Research shows that the application of salicylic acid (Morovvat et al 2021) reported treatment of potatoes showed a significant effect on the water supply status of the plants; the effect of salicylic acid on irrigation treatment 60 and 80% showed an increase in potato yields under severe drought stress conditions. The best yield treatment was salicylic acid treatment with 100% irrigation.…”
Section: Interaction Effect Between Ds and Sa On Growth And Photosynt...mentioning
confidence: 99%